2022
DOI: 10.21037/atm-21-5699
|View full text |Cite
|
Sign up to set email alerts
|

Does fructose have a protective role on migraine?—experimental evidence in a rat model of metabolic syndrome under omega-3 supplementation

Abstract: Background: Migraine is a highly disabling disease, for which current therapies are limited to symptom alleviation. There is compelling evidence linking migraine with metabolic disorders, but the causal relationship is not clear. Omega-3 (n-3) fatty acids have anti-inflammatory properties, with clear benefits in metabolic disorders, but its effects on migraine remains to be tested. We hypothesized that fructose-induced metabolic syndrome could aggravate migraine by increasing neuroinflammation and that n-3 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 126 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…Based on a classic migraine rat model established by repeated dural infusions of inflammatory soup (IS), Xin Dong et al [ 38 ] observed abnormal mitochondrial dynamics and damaged mitochondrial biogenesis in the TG. Based on NTG-induced CM model, Barbosa IR et al [ 43 , 44 ] reported that mitochondrial metabolism was influenced by NTG in the brain cortices and TG. However, fructose supplementation led to changes in brain metabolism, lessened the migraine-like painful symptoms, and reduced serum CGRP levels, which might imply that an increased energy supply could be somewhat favorable in migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a classic migraine rat model established by repeated dural infusions of inflammatory soup (IS), Xin Dong et al [ 38 ] observed abnormal mitochondrial dynamics and damaged mitochondrial biogenesis in the TG. Based on NTG-induced CM model, Barbosa IR et al [ 43 , 44 ] reported that mitochondrial metabolism was influenced by NTG in the brain cortices and TG. However, fructose supplementation led to changes in brain metabolism, lessened the migraine-like painful symptoms, and reduced serum CGRP levels, which might imply that an increased energy supply could be somewhat favorable in migraine.…”
Section: Discussionmentioning
confidence: 99%